Brands as cultural resources in children's peer culture. Issue 3 (4th May 2017) - Hémar-Nicolas, Valérie; Rodhain, Angélique
ABSTRACT: This article examines how children collectively appropriate brands as cultural resources. From the New Childhood Studies perspective, an ethnographic study was conducted in schools to investigate the engagement of 10- to 11-year-old children in brand culture. The findings demonstrate that, through a process similar to Corsaro's model of interpretive reproduction, children do not simply reproduce brand culture; instead, they actively use branding to fuel their peer culture. Mastering and manipulating brands are thus sources for integration or exclusion within the peer group and for differentiation from the adult world. We show the paradoxical impacts of branding on children's well-being and participate in the debate on their vulnerability to marketing by highlighting how they deploy brand culture to interact in their social spheres, with the consequence being that their would-be empowerment remains entangled in the "brandscape." Last, we contribute to a better understanding of the concept of culturally based brand literacy.